BENTUK MAGIS DALAM NOVEL NEGERI PARA ROH KARYA ROSI L. SIMAMORA: KAJIAN REALISME MAGIS WENDY B. FARIS - Andriani, Alda Alif; Rapi, Muhammad; Abidin, Aslan (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2025)
Research entitled “Magical Form in the Novel Negeri Para Roh by Rosi L. Simamora: A Study of Magical Realism by Wendy B. Faris” sim to describe the characteristics of magical realism and the dominant magical realism characteristics in the novel Negeri Para Roh by Rosi L. Simamora. which was studied using Wendy B. Faris's theory of magical realism. This study uses a descriptive qualitative research method to collect and filter data. Based on the results of the analysis using five characteristics of magical realism, novel Negeri Para Roh by Rosi L. Simamora fulfills five characteristics of magical realism. Magical realism narrated of novel not only loaded with Faris's magical realism, but also strengthens a belief of the Asmat tribe. The dominant characteristic in the study is the characteristic of unsettling doubt. This is based on the narrative contained in the novel Land of the Dominant Spirits that brings the reader to the point of doubt.